Clinical characteristics and course of patients with diabetes entering cardiac rehabilitation. Issue 2 (February 2015) - Giallauria, Francesco; Fattirolli, Francesco; Tramarin, Roberto; Ambrosetti, Marco; Griffo, Raffaele; Riccio, Carmine; De Feo, Stefania; Piepoli, Massimo Francesco; Vigorito, Carlo; ,
Abstract: Background: Using data from the Italian SurveY on carDiac rEhabilitation (ISYDE-2008), this study provides insight into the level of implementation of Cardiac Rehabilitation (CR) in patients with diabetes. Methods: Data from 165 CR units were collected online from January 28th to February 10th, 2008. Results: The study cohort consisted of 2281 patients (66.9 ± 12 yrs); 475 (69.7 ± 10 yrs, 74% male) patients with diabetes and 1806 (66.2 ± 12 yrs, 72% male) non-diabetic patients. Compared to non-diabetic patients, patients with diabetes were older and showed more comorbidity [myocardial infarction (32% vs. 19%, p  < 0.0001), peripheral artery disease (10% vs. 5%, p  < 0.0001), chronic obstructive pulmonary disease (20% vs. 11%, p  < 0.0001), chronic kidney disease (20% vs. 6%, p  < 0.0001), and cognitive impairment (5% vs. 2%, p  = 0.0009), respectively], and complications during CR [re-infarction (3% vs. 1%, p  = 0.04), acute renal failure (9% vs. 4%, p  < 0.0001), sternal revision (3% vs. 1%, p  = 0.01), inotropic support/mechanical assistance (7% vs. 4%, p  = 0.01), respectively]; a more complex clinical course and interventions with less functional evaluation and a different pattern of drug therapy at hospital discharge. Notably, in 51 (3%) and in 104 (6%) of the non-diabetic cohort, insulin and hypoglycemic agents were prescribed, respectively, at hospital discharge from CR suggesting a careful evaluation of the glycemic metabolism during CR program, independent of the diagnosis at the admission. Mortality was similar among diabetic compared to non-diabetic patients (1% vs. 0.5%, p  = 0.23). Conclusions: This survey provided a detailed overview of the clinical characteristics, complexity and more severe clinical course of diabetic patients admitted to CR.